Application of Problem-based Learning in Efforts to Build Mathematical Literacy Skills - Smith, George; Putri Liowardani, Adelia; Permadi, Hendro; Anita, Yuli (KnE Social Sciences, 2023)
Mathematical literacy ability is the ability that a person has in formulating, using, and interpreting mathematics in a variety of concepts. From the results of diagnostic tests conducted at the beginning of the 7.1 grade learning year at SMPN 3 Malang, it was found that more than 50% of students were not maximal in applying mathematical concepts in solving a mathematical problem. This can happen due to a misunderstanding of the problem or also a mathematical concept that is not used to being used. The use of learning by using problem-based learning, which is carried out in 2 cycles and discusses material regarding number operations (multiplication and division of integers) is applied to build students’ mathematical literacy skills on number operations material. This study contains actions that are adapted to the syntax of problem-based learning and indicators at level 2-3 PISA mathematical literacy abilities. The results of this study applying the problem-based learning model adapted to the PISA mathematical literacy ability indicators obtained a very significant increase in score from 50.01 to 91.43 and at the evaluation stage, the results increased from 44% to 75.86%. It can be stated that the application of problem-based learning model if adapted to PISA’s mathematical literacy ability indicators can build mathematical literacy skills. Keywords: problem-based learning, mathematical literacy, operation of integers